IMPLEMENTASI PROGRAM RUMAH LAYAK HUNI DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Muhammad Aldo Saputra; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This thesis research is located in the Department of Housing, Settlement and Land in Bengkalis Regency. The purpose of this thesis is to find out and describe the extent of the Implementation of the Program for the Construction of Livable Houses in the District of Mandau. The focus of research in this study consisted of elements of the implementer, the program carried out and the target groups as well as the factors that hampered the Implementation of the Livable Houses Program in Mandau District, Bengkalis Regency.Data collection techniques carried out by means of library research and field research consisting of observations, interviews and documentation, while the informants were taken by purposive sampling. This type of research is descriptive and will be analyzed qualitatively.From the research results it is known that the Implementation of the Livable Living Program in the District of Mandau is quite good with a long process starting from the planning, implementation, survey and completion of activities carried out by the implementor in the village, sub-district to district and community beneficiaries. With a significant change from the houses of the beneficiaries, the Occupied Housing Program. Keywords: Implementation, Programs, Livable Houses